From self-directed learning to postmodernist thought in adult education: Relocating our object of theory and practice - Michael Collins (Adult Education Research Conference, 1994)
This paper makes a case for abandoning the "andragogical consensus" and its pedagogical trappings (a.k.a. SDL). Questions are raised about the potential of postmodernist critique and its denial of reason.